IJCM_66A: Beliefs, perceptions, and practices of mothers of under-five children towards control of childhood anemia in selected urban and rural areas of Puducherry - An explanatory mixed methods study. - Sridevi; Tamilselvan; Jayalakshmy (Wolters Kluwer Medknow Publications, 2024)
Background: Anaemia is a significant public health issue that affects different age groups, mainly children under five. A mother's knowledge, attitudes, and practices are often associated with the health status of children Objective: The study aimed to assess mothers' knowledge, attitudes, and practices towards childhood anaemia control, the status of IFA consumption among under-five children in Puducherry, and explore socio-cultural beliefs and perceptions about childhood anaemia. Methodology: A community-based cross-sectional study was conducted in selected urban and rural areas, where Anganwadi centres were selected through simple random sampling. A pre-validated semi-structured questionnaire was used to collect data from mothers of children under five. In-depth interviews were conducted to explore socio-cultural beliefs and perceptions of childhood anaemia. Results: According to the study, the majority of participants were aware of the causes (89.5%) and symptoms (90.3%) of anaemia, as well as the consequences during pregnancy (80.7%) and child growth risks (72.3%). However, the knowledge of health risks to the child if the mother is anaemic during pregnancy was known to only 64.0% of mothers. While most participants were aware of iron-rich foods, the knowledge of the practice of providing these foods was less widespread. Additionally, only 28.4% of children receive adequate IFA supplements. Conclusion: Though knowledge, attitude, and practices have improved, they are still inadequate to reduce the anaemia burden. Only one in three children received adequate IFA supplements. Adherence to the correct dosage of IFA supplementation needs further awareness and emphasis.